2022
DOI: 10.3390/brainsci12091193
|View full text |Cite
|
Sign up to set email alerts
|

Olive- and Coconut-Oil-Enriched Diets Decreased Secondary Bile Acids and Regulated Metabolic and Transcriptomic Markers of Brain Injury in the Frontal Cortexes of NAFLD Pigs

Abstract: The objective of this study was to investigate the effect of dietary fatty acid (FA) saturation and carbon chain length on brain bile acid (BA) metabolism and neuronal number in a pig model of pediatric NAFLD. Thirty 20-day-old Iberian pigs, pair-housed in pens, were randomly assigned to receive one of three hypercaloric diets for 10 weeks: (1) lard-enriched (LAR; n = 5 pens), (2) olive-oil-enriched (OLI, n = 5), and (3) coconut-oil-enriched (COC; n = 5). Pig behavior and activity were analyzed throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 114 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Accumulated evidence indicates an association between NAFLD and neuro-pathologies, impacting both cognitive function and brain volume. Animal studies have demonstrated NAFLD effects on thalamic energy metabolism and hippocampal structure [6,9,49]. We used genetic tools for liver fat and liver volume to represent the liver health status in NAFLD [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence indicates an association between NAFLD and neuro-pathologies, impacting both cognitive function and brain volume. Animal studies have demonstrated NAFLD effects on thalamic energy metabolism and hippocampal structure [6,9,49]. We used genetic tools for liver fat and liver volume to represent the liver health status in NAFLD [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD affects the central nervous system (CNS) via a variety of mechanisms, including metabolic disruptions, blood-brain barrier impairment, systemic inflammation, gut microbiota imbalances, and bile acid abnormalities [4,8]. One study found specific dietary interventions with certain oils could regulate the expression of some genes to preserve neuron quantity and synaptic density in a porcine model of NAFLD [9]. Neurodegenerative diseases often involve neuronal loss and abnormalities in cortical structure, identifiable through T1-weighted MRI [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic data was analyzed using the %polynova_1way SAS macro [33]. Transcriptomic data were analyzed using a generalized linear model with an assumption of a negative binomial distribution of gene counts and using a 5% FDR threshold in edgeR-Bioconductor packageBio package" as previously described [34]. The Database for Annotation, Visualization, and Integrated Discovery (DAVID) software version 6.8 [35] was used to perform functional enrichment analyses on differently expressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…The results included improvements in various biochemical markers related to inflammation and brain function, suggesting potential neuroprotective effects. [197] Olive oil…”
Section: Molecular Effectsmentioning
confidence: 99%